The proscription or listing of terrorist organisations: understanding, assessment, and international comparisons - Jarvis, Lee (Terrorism and political violence, 2018)
This article serves as an introduction to this Special Issue on the banning or proscription of terrorist organisations around the world. It begins by arguing for greater attention to proscription powers because of their contemporary ubiquity, considerable historical lineage, implications for political life, and ambiguous effectiveness. Following an overview of the Issue’s questions and ambitions, the article discusses five themes: key moments of continuity and change within proscription regimes around the world; the significance of domestic political and legal contexts and institutions; the value of this power in countering terrorism and beyond; a range of prominent criticisms of proscription, including around civil liberties; and the significance of language and other symbolic practices in the justification and extension of proscription powers. We conclude by sketching the arguments and contributions of the subsequent articles in this Issue.